Significance of Torrefaction Effect on Energy Properties Palm Kernel Shell - Dirgantara, Made; Karelius, Karelius; Rumbang, Nyahu (Universitas Negeri Malang, 2023)
The process of torrefaction is a thermochemical process that is widely used for the conversion of biomass into renewable fuels. In this study, the significance of temperature was determined by carrying out the torrefaction process at temperatures ranging from 275 to 350 degrees Celsius with a fixed residence time of 60 minutes. To ascertain the impact of time on the process, the torrefaction procedure was conducted over a residence time of 20 to 60 minutes at 300°C. Increasing the torrefaction temperature can substantially increase the palm kernel shell's calorific value, decrease water content, decrease volatility, increase fixed carbon, especially from 275 oC to 325 oC, and decrease ash content from 275 oC to 300 oC. Increasing the torrefaction residence time can significantly increase the palm kernel shell's calorific value from 20-40 minutes, decrease ash content and volatile content, and increase fixed carbon from 20-30 minutes. The residence time did not affect the water content in torrefaction temperature at 300 oC. The statistical analysis revealed that temperature and residence time have a substantial impact on the heating value and proximate analysis.